ANALISIS YURIDIS TINDAKAN PEMALAKAN YANG DILAKUKAN OKNUM POLISI: PERSPEKTIF HUKUM PIDANA DAN DISIPLIN KEPOLISIAN - I Made Billy Dalem Kriswara; Subhan Zein Sgn (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Law enforcement is an essential task of the police as a symbol of social justice. However, the rampant cases of extortion or blackmail by police officers, such as those that befell Guru Supriyani, a DWP audience, the son of a Prodia boss, and a couple in Semarang, have damaged the institution's image and eroded public trust. This study analyzes disciplinary enforcement regulations and legal analysis of extortion by police officers in Indonesia. This study uses a normative legal research method with a statutory, case, and conceptual approach, as well as qualitative analysis. The results of the study show that the Regulation of the Republic of Indonesia National Police Number 7 of 2022 concerning the Code of Professional Ethics and the Indonesian National Police Code of Ethics Commission (KEPP) are the main basis for enforcing discipline, detailing ethical standards, prohibiting abuse of authority (including extortion), and regulating disciplinary sanctions up to dishonorable discharge (PTDH). In addition, Government Regulation Number 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police is also the basis for taking action against general disciplinary violations.